La inobservancia de la garantía del derecho a la identidad incide en el ejercicio de derechos constitucionales. - Quishpe Sarmiento, Patricio Xavier (2023)
The purpose of this work is to understand the importance of the fundamental and constitutional right of identity, having as its essence the protection of people, the protection of their rights and that public institutions do not violate these rights, that do not prevent the exercise of the same. Having to start from dignity, because respect for the innate rights of people must be recognized and they must be protected by the authorities, the right to identity is the starting point to demand compliance with other rights.